ANALYSIS OF SCIENCE TEACHERS' DIFFICULTIES IN IMPLEMENTING THE INDEPENDENT CURRICULUM IN JUNIOR HIGH SCHOOL AND EQUIVALENT IN WEST ACEH DISTRICT - Irsyadi, Ilham Firnando; Wahid, Mulyadi Abdul; Fitriyawany, Fitriyawany (Universitas Islam Negeri Ar-Raniry, 2025)
The independent learning curriculum is implemented in 2021/2022 and not all schools have implemented this independent curriculum so that there are still few references, especially at the junior high school level. Physics teachers in implementing the Independent Curriculum at SMPN 1 Susoh Aceh Barat Daya, SMPN 3 Susoh Aceh Barat Daya, and MTsN 1 Aceh Barat Daya face obstacles, namely teachers do not have experience with the concept of the Independent Learning Curriculum. This study aims to find out what are the difficulties of science teachers in implementing the independent curriculum and how science teachers overcome them in implementing the independent curriculum. This study uses a descriptive research method with a qualitative research method approach. The results of the study indicate that the difficulties of science teachers in implementing the independent curriculum that occur in the application of Physics subjects at SMPN 1 Susoh Aceh Barat Daya, SMPN 3 Susoh Aceh Barat Daya, and MTsN 1 Aceh Barat Daya are in planning, implementing learning and assessment. Science teachers' efforts to overcome this include attending meetings with (KKG), attending training, coordinating with fellow teachers, teachers do not require students to memorize but must understand the material, teachers write the material on the board and make student worksheets, students take notes, continue class projects at home, look for references on assessments and attend training on implementing the Independent Learning Curriculum.